Quelques propositions - Rémillard, Gil (Les Cahiers de droit, 1985)
Professor Rémillard questions the failure of the Senate after dealing with the debate on its reform within the context of Rapatriation of the Constitution. The Fathers of Confederation intended the Senate to represent and protect regional interests. It has enough powers to be effective but fails to manage its very own powers. The passivity might explained by the fact that senators have been too bound by party discipline to be reliable. An extended reform of the Senate would certainly be better than its abolition. First, the Senate should fight to keep democracy alive and to counterbalance the powers of the House of Commons. It should be an effective guardian of regional interests in the dual Canadian context. The author suggests that the reform of the Senate should be done within the limits of an entire reform of federal institutions. This would help Canadian federalism preserve its parliamentary system.